Green Fuel: Improvement of Engine Performance using Water-in-Diesel Emulsion (WiDE) with a Small Percentage of Hydrogen - Mohd Thulus, Shahmirul Azri (IRC, 2016)
Diesel engines are utilized as the main propulsion power source for both in-area and marine transportation primarily in view of their basic, inflexible structure and high efficiency. Diesel engines are broadly utilized in automotive industries. In any case, the pollutants discharged from diesel engines, specifically nitrogen oxides and particulate matter, which are harmful to the soundness of living creatures and the natural environment, have been perceived as a major air contamination source in metropolitan territories. One of the methods to reduce the emissions from the diesel engine is using water-in-diesel as fuel. Hydrogen is added into the combustion chamber at intake manifold due to the decreasing in the performance of diesel engine when using water-in-diesel as fuel.